Evaluation of four modelling techniques to predict the potential distribution of ticks using indigenous cattle infestations as calibration data - Zeman, Petr; Lynen, Godelieve (Experimental & applied acarology, 2006)
Efficient tick and tick-borne disease control is a major goal in the efforts to improve the livestock industry in developing countries. To gain a better understanding of the distribution and abundance of livestock ticks under changing environmental conditions, a country-wide field survey of tick infestations on indigenous cattle was recently carried out in Tanzania. This paper evaluates four models to generate tick predictive maps including areas between the localities that were surveyed. Four techniques were compared: (1) linear discriminant analysis, (2) quadratic discriminant analysis, (3) generalised regression analysis, and (4) the weights-of-evidence method. Inter-model comparison was accomplished with a data-set of adult Rhipicephalus appendiculatus ticks and a set of predictor variables covering monthly mean temperature, relative humidity, rainfall, and the normalised difference vegetation index (NDVI). The data-set of tick records was divided into two equal subsets one of which was utilised for model fitting and the other for evaluation, and vice versa, in two independent experiments. For each locality the probability of tick occurrence was predicted and compared with the proportion of infested animals observed in the field; overall predictive success was measured with mean squared difference (MSD). All models exhibited a relatively good performance in configurations with optimised sets of predictors. The linear discriminant model had the least predictive success (MSD>or=0.210), whereas the accuracy increased in the quadratic discriminant (MSD>or=0.197) and generalised regression models (MSD>or=0.173). The best predictions were gained with the weights-of-evidence model (MSD>or=0.141). Theoretical as well as practical aspects of all models were taken into account. In summary, the weights-of-evidence model was considered to be the best option for the purpose of predictive mapping of the risk of infestation of Tanzanian indigenous cattle. A detailed description of the implementation of this model is provided in an annex to this paper.
Keywords: Cattle; Regression Analysis; Animals; skot; biologické modely; Models, Statistical; Rhipicephalus; Tanzania; infestace klíšťaty; Models, Biological; statistické modely; regresní analýza; Tanzanie; nemoci skotu; diskriminační analýza; Cattle Diseases; Discriminant Analysis; zvířata; Tick Infestations